Analisis Peran Pendidikan Karakter di Era Digitalisasi - Siti Alpiah; Tiodora Sigalingging; Helen Dwi Anggraeni; Melani Putri Maria Sianturi; Fransiska Christiyani Wulandari; Laura Nianti Lestari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The development of digital technology has brought great changes in the world of education, especially in the way of shaping students' character. On the one hand, digitalization provides easy access to information, supports innovation, and expands learning opportunities. However, on the other hand, various challenges arise such as the spread of false information, cyberbullying, a decline in communication ethics, and a reduction in direct social interaction. This research aims to explore the role of character education in facing challenges in the digital era. The method used was a literature review by analyzing twenty scientific sources, including SINTA- indexed national journals, international journals, and books relevant to this topic. The findings of the study show that character education is very important in shaping students' responsible attitudes, discipline, integrity, and digital literacy skills. The implementation of the Independent Curriculum through strengthening the Pancasila Student Profile also supports the development of characters that are responsive to technological advances. In addition, the success of character education requires cooperation between schools, homes, and the community to guide students in using technology wisely. That way, character education becomes an important basis in creating a generation that is not only capable of technology, but also has strong morals and ethics in the digital era.